ПДС-алгоритмы и труднорешаемые задачи комбинаторной оптимизации - Згуровский, М.З.; Павлов, А.А.; Мисюра, Е.Б. (Системні дослідження та інформаційні технології, 2009)
Формулируются базовые принципы построения ПДС-алгоритмов. Приводятся обобщения повышения эффективности их использования. Анализируется возможность создания новых ПДС-алгоритмов на основе существующих. Формулюються базові принципи побудови ПДС-алгоритмів. Наводяться узагальнення по підвищенню ефективності їхнього використання. Аналізується можливість створення нових ПДС-алгоритмів на основі існуючих. Based on the analysis of PDC-algorithms for intractable combinatorial optimization problems, general principles of their building are formulated and generalizations about increasing the effectiveness of their using are given. A possibility of constructing new PDC-algorithms on the basis of the existed ones is analyzed.